[PP.37.05] ASSOCIATION OF AORTIC PULSE WAVE VELOCITY WITH MINERAL METABOLISM FACTORS AND BLOOD PRESSURE IN UNTREATED CHINESE PATIENTS. (September 2016) - Cheng, Y.B.; Li, L.H.; Guo, Q.H.; Sheng, C.S.; Huang, Q.F.; Li, F.K.; Zhang, D.Y.; Wang, J.G.; Li, Y.
Abstract : Objective: Disorders of mineral metabolism predicted incidence of cardiovascular events in various clinical settings, possibly because that arterial stiffness mediate this pathway in part. We investigated the interrelationship between mineral metabolism factors and carotid-femoral PWV, and compared the effect sizes of blood pressure and mineral factors with carotid-femoral PWV in untreated Chinese. Design and method: Consecutive untreated outpatients referred for ambulatory blood pressure monitoring were recruited. Serum parathyroid hormone (PTH) and 25-hydroxyvitamin D were measured with electrochemiluminescence immunoassay, and 24-h urinary calcium and phosphate excretion were determined. Carotid-femoral PWV was measured using the SphygmoCor (AtCor, Australia) device. Pearson's correlation, single and multiple regressions were applied for analyses. Results: The 1063 participants (mean age 51 years) included 539 (50.7%) women, 658 (61.9%) patients with ambulatory hypertension, 75 (7.1%) patients with arterial stiffness defined as a carotid-femoral PWV over 10 m/s. After standardization for sex, age, body mass index, fasting plasma glucose, serum total and HDL cholesterol, all 24-h blood pressure parameters, including systolic and diastolic blood pressure, mean and pulse pressures, were significantly (r > 0.21, P < 0.001) associated with carotid-femoral PWV, and for mineral metabolism factors, none (P > 0.22) was associated with carotid-femoral PWV, except for serum PTH (r = 0.08, P = 0.008). In fully adjusted model including aforementioned risk factors and both 24-hour systolic blood pressure and PTH, 24-h blood pressures (r > 0.21, P < 0.001) and serum PTH (r = 0.06, P = 0.031) remained significantly associated with carotid-femoral PWV. Indeed, per SD (12 mmHg) increment of 24-h systolic blood pressure and each double of serum PTH were associated with the increase in carotid-femoral PWV by 0.45 (0.38–0.52) m/s and by 0.19 (0.049–0.32) m/s, respectively. The effect size associated with 24-hour systolic blood pressure was statistically (P < 0.001) larger than that with PTH. Conclusions: Among the studied mineral metabolism factors, only serum PTH, was associated with aortic stiffness, and blood pressure might play a more significant role than PTH in arterial stiffening.